Technological study on the flotation process of Manganese Ore - Ts, Zagarzusem; N, Sugir-Erdene; B, Orgilbayar; S, Sukhbat; Ts, Soyolmaa; B, Unursaikhan; D, Baasanjav; L, Jargalsaikhan; E, Otgonjargal (Bulletin of the Institute of Chemistry and Chemical Technology, 2020)
This study demonstrated the importance of appropriate flotation conditions and reagent dosage for the separation of standard manganese concentrates from low-grade manganese ores. The research object used Unagad manganese ore located in Dornogovi province. The main mineral of manganese ores was pyrolusite (MnO2). According to the chemical element analyses, the content of manganese in the primary ore was Mn-17.31%. XRD analyses revealed minerals such as quartz, pyrolusite, albite, anorthite, anorthoclase, orthoclase, and hausmannite. This study conducted the beneficiation of manganese ore by the froth flotation method. Manganese ore beneficiation tests were performed for the flotation method under the following conditions: the collector dosage with 900 g/t, 1100 g/t, 1300 g/t, 1500 g/t, and 1700 g/t, the dosage of the depressant as 570 g/t, 670 g/t, 770 g/t, and 870 g/t, and the frother with 900 g/t, pH value 8, the grade of -0.074 mm was 60%, 70%, 80%, 90% respectively. Beneficiation tests performed in the optimum conditions resulted in concentrate with Mn = 32.37%, the recovery was 57.33%, and the yield was 30%. As a result of the flotation enrichment of manganese ore, а concentrate containing 32.37% manganese was obtained. Манганы хүдрийг флотацийн аргаар баяжуулах технологийн судалгаа Хураангуй: Энэхүү судалгаагаар бага агуулгатай манганы хүдрээс стандартын шаардлага хангасан манганы баяжмалыг гарган авахад флотацийн зохистой горим, урвалжийн зарцуулалт хэрхэн нөлөөлж байгааг тогтоов. Судалгааны объектоор Дорноговь аймгийн нутагт орших Унагадын манганы ордын хүдрийг ашигласан бөгөөд хүдрийн голлох эрдэс нь пиролюзит юм. Элементүүдийн химийн шинжилгээгээр анхдагч хүдэр дэх манганы агуулга 17.31% байна. Рентген дифрактометрийн шинжилгээгээр кварц, пиролюзит, альбит, анортит, анортоклаз, ортоклаз, гаусманит зэрэг эрдсүүд байгаа нь тогтоогдсон. Манганы хүдрийг флотацийн аргаар баяжуулах цуврал туршилтуудыг цуглуулагчийн зарцуулалт 900 г/т, 1100 г/т, 1300 г/т, 1500 г/т, 1700 г/т, дарагчийн зарцуулалт 570 г/т, 670 г/т, 770 г/т, 870 г/т, хөөсрүүлэгч 900 г/т, рН-8, ширхэглэлийн хэмжээг -0.074 мм ангийн агуулга 60%, 70%, 80%, 90% гэсэн нөхцлүүдэд явуулсан. Туршилтын дүнд цуглуулагчийн хэмжээ 1500 г/т, хөөсрүүлэгч 900 г/т, дарагч 670 г/т, -0.074 мм ангийн агуулга 70%, рН-ийн утга 8 гэсэн хамгийн тохиромжит нөхцөлд баяжмал дахь металл авалт 57.33%, гарц 30% байж, харин Mn-ний агуулга 32.37%-тай баяжмал гарав. Түлхүүр үг: Манганы баяжмал, флотаци, олейны хүчил, натрийн силикат